PROGRAM PENGEMBANGAN “PROTAP” (PRODUK DARI TANAMAN ASLI PAPUA) SEBAGAI PROGRAM PEMBERDAYAAN EKONOMI BIDANG KESEHATAN PADA MASYARAKAT KAMPUNG TOBATI-ENGGROS KOTA JAYAPURA - Puguh Sujarta; Septriyanto Dirgantara (LPPM Uncen, 2018)
Indonesia is a country that has a wealth of flora number two in the world after Brazil and is believed to have a variety of plants tha can be used as medicine.The use of herbs fo treatment, especially the use of medicines that have been integrated into formal health services in Indonesia is still low compared to some other Asian countries. Papuan medicinal plants have superior characteristic that are different from other provinces in Indonesia. The usage of potential natural products as medicines for Papuan communities are selected by a good understanding of herbal medicine. The potential of biological acticity from natural resources provides a great opportunity to developing this program. In this case, the activities of the Community Engagement activities with the title Development of